PEMBERDAYAAN MASYARAKAT DESA MARUAT MELALUI PROGRAM EDUKASI, KESEHATAN, DAN PENGEMBANGAN UMKM: Community Empowerment in Maruat Village through Education, Health, and MSME Development Programs - Triyoga, Anwar Ibrahim; Mumek, Mathew Geovani; Mukhlis, Amal Nur; Daniel, Ulen; Rahmayani, Eva; Hardin, Firnawati; Yulianti, Andini; Hariadi, Muhammad Al Fitho; Istiqomah, Nilam Cahya; Kristanti, Retno; Azzahra, Caesaria Maulaya (Program Studi Sastra Indonesia Universitas Mulawarman, 2025)
Abstract: The Community Service Program (KKN) in Maruat Village was carried out as a form of community engagement aimed at improving the quality of life through education, health, and the empowerment of micro, small, and medium enterprises (MSMEs). This program was conducted over one month, involving 10 university students, village officials, and the active participation of local residents. A participatory approach was employed through socialization, training, and continuous assistance. In the field of education, students implemented programs such as etiquette awareness campaigns, saving habits promotion, English and Natural Sciences teaching, as well as Quran recitation mentoring for children. In the health sector, activities included the organization of integrated healthcare posts (posyandu) for toddlers, adolescents, and the elderly, stunting prevention socialization, and training on producing mosquito repellent spray using lemongrass. Meanwhile, in the area of MSME empowerment, the program focused on training in coconut oil production, palm sugar processing, coconut fiber handicrafts, and supporting local business promotion through banners, posters, and the inclusion of business locations on Google Maps. The results demonstrated positive changes, including increased student learning motivation, greater community awareness of health, and strengthened enthusiasm among local entrepreneurs in developing their products. This program contributed to enhancing community capacity in education, health, and the local economy in an integrated manner. Thus, community service based on active participation proved effective in fostering sustainable social transformation and providing long-term benefits for the independent development of Maruat Village. Keywords: Education; Empowerment; Health; Maruat; Micro Small and Medium Enterprises. Abstrak: Kegiatan Kuliah Kerja Nyata (KKN) di Desa Maruat dilaksanakan sebagai bentuk pengabdian kepada masyarakat dengan tujuan meningkatkan kualitas hidup warga melalui bidang pendidikan, kesehatan, dan pemberdayaan usaha mikro kecil menengah (UMKM). Program ini berlangsung selama satu bulan dengan melibatkan 10 mahasiswa, perangkat desa, serta partisipasi aktif masyarakat setempat. Pendekatan yang digunakan adalah partisipatif, melalui sosialisasi, pelatihan, dan pendampingan berkelanjutan. Pada bidang pendidikan, mahasiswa melaksanakan program sosialisasi sopan santun, gerakan gemar menabung, pengajaran mata pelajaran Bahasa Inggris dan Ilmu Pengetahuan Alam, serta pendampingan mengaji bagi anak-anak. Pada bidang kesehatan, kegiatan mencakup penyelenggaraan posyandu balita, remaja, dan lansia, sosialisasi mengenai pencegahan stunting, serta pelatihan pembuatan cairan semprot anti nyamuk berbahan dasar serai. Adapun pada bidang pemberdayaan UMKM, kegiatan difokuskan pada pelatihan produksi minyak kelapa, gula semut, kerajinan serat kelapa, serta dukungan promosi usaha lokal melalui spanduk dan pencantuman lokasi usaha di Google Maps. Hasil kegiatan menunjukkan adanya peningkatan motivasi belajar siswa, meningkatnya kesadaran masyarakat mengenai pentingnya kesehatan, serta bertumbuhnya semangat pelaku usaha dalam mengembangkan produk lokal. Program ini berimplikasi pada penguatan kapasitas masyarakat dalam bidang pendidikan, kesehatan, dan ekonomi lokal secara terpadu. Dengan demikian, pengabdian masyarakat berbasis partisipasi aktif terbukti mampu mendorong perubahan sosial yang berkelanjutan dan memberi bekal bagi masyarakat Desa Maruat untuk mengembangkan potensi secara mandiri di masa depan. Kata kunci: Kesehatan; Maruat; Pemberdayaan; Pendidikan; UMKM.